2015
DOI: 10.1007/s00259-015-3243-y
|View full text |Cite
|
Sign up to set email alerts
|

Central serotonin transporter availability in highly obese individuals compared with non-obese controls: A [11C] DASB positron emission tomography study

Abstract: The overall finding of a lack of significantly altered 5-HTT availability together with its high variance in obese individuals justifies the investigation of individual behavioral responses to external and internal cues which may further define distinct phenotypes and subgroups in human obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Furthermore, LDA based on the NAT-rich LC revealed a relatively high power to distinguish obese from non-obese humans. Together with this, correlative analyses point towards a distinctive regional distribution of NAT availability between obese and non-obese individuals with more robust associations in obese individuals as we have found also for serotonin transporters [26]. This observational finding should be discussed with other parameters of neural connectivity in the near future to obtain specific group characteristics.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, LDA based on the NAT-rich LC revealed a relatively high power to distinguish obese from non-obese humans. Together with this, correlative analyses point towards a distinctive regional distribution of NAT availability between obese and non-obese individuals with more robust associations in obese individuals as we have found also for serotonin transporters [26]. This observational finding should be discussed with other parameters of neural connectivity in the near future to obtain specific group characteristics.…”
Section: Discussionsupporting
confidence: 68%
“…First, the majority of our subjects were premenopausal women and our results remain to be validated in different age groups. Second, we studied men and women, while gender differences have been observed for striatal DAT [51] and diencephalic SERT binding [52], but not for hypothalamic SERT binding [31]. However, analyses of our results on SERT and DAT did not change after excluding the male subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Previous imaging studies showed a negative correlation between BMI and diencephalic SERT binding in some [6] but not all [29, 30, 31] studies, and data on insulin sensitivity were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The same brain regions reflecting tryptophan fluctuation and fat mass in our findings supported the findings above, suggesting the modulating role of body composition in serotonergic neurotransmission, or even the dysregulation of serotonergic system as a probable pathophysiologic mechanism in obesity. However, in another two studies the SERT availability showed no significant or negative association between non-obese and obsess subjects [47,49], which may implicate the lower reliability of the parameter BMI in predicting serotonergic system and risk decision behaviors. 1 6 In our study, we investigated only normal weight male participants without insulin resistant.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies using positron emission tomography (PET) or single-photon emission computed tomography (SPECT) suggested associations between body mass and 5-HT receptors density or transporter (SERT) availability in broad cortical regions (i.e., OFC, DLPFC, parietal lobule,) and subcortical regions (i.e., striatum and thalamus) [46][47][48][49]. Across normal-weight and obese people, positive correlations have been demonstrated between BMI, and global brain SERT availability, 5-HT 2A receptor binding across cerebral cortex, 5-HT 4 receptor binding in reward circuits [46,48,49].…”
Section: Discussionmentioning
confidence: 99%